Patients’ Operative Care Knowledge and Desire for Information About Surgery and Anesthesia - Gurung, Renu; Acharya, Binita; Shakya, Bigen M (Journal of Institute of Medicine Nepal, 2021)
Introduction Good communication between patients and health professionals and sharing of information on operative procedures form the basis of informed consent. The objective of the study was to assess our patients’ information on the operative procedures and their desire for information about surgery and anesthesia. Methods This was a descriptive cross-sectional study done in one of the academic institutes of Nepal. The sample size calculated was 422. A simple random sampling by proportionate method was used. Patients between 18 to 80 yrs. scheduled for elective surgeries were included in the study. The questionnaires were read by anesthesiologist to the participants after preanesthetic check-up just before scheduled operation in the preparation room. Patients were requested to complete a 100 mm visual analogue scale by marking a cross to indicate level of anxiety on a spectrum of 'not anxious ' to 'extremely anxious'. Results The final number of participants were 404. About 21.53 % of the patients did not know about the type of operation that they were about to undergo and 19.8 % of the patients were unaware whether they would be put into unconscious state or not. More than half did not know about duration of surgical procedure (61.88%), time of resuming daily activities after surgery (60.64%), duration of stay in hospital (48.76%), pain after surgery (47.77%). There was positive correlation between the information and level of education (p<0.001) and patients with past history of surgeries (p=0.001). Conclusion The patients lacked information on operative care especially regarding duration of surgical procedure, duration of stay in hospital and time required for resuming daily activities.